Facing twenty-first century challenges on the foundation of panchsheel - Ranganathan, C.V. (2004)
The prodamation of Panhsheel as the basis of their foreign policies by the governments of India and China in 1954 led to the launch of the Non-Aligned Movement in the wake of the 1955 Bandung Conference, Russia since then has consistently expressed support for those principles which provide a useful regional and global framework for the prevention of terrorism, international stability and economic cooperation. - Reproduced.
Keywords: Panchsheel; International relations